AN ANALYSIS OF MEDIA USED IN TEACHING ENGLISH THROUGH ONLINE LEARNING IN THE COVID-19 PANDEMIC AT PUBLIC VOCTIONAL HIGH SCHOOLS AT LUBUKLINGGAU - muhammad aldiansyah (JURNAL LINER (Language Intelligence and Educational Research), 2022)
Research by Muhammad Aldiansyah, SRN 2115030 entitled “An Analysis of Media Used in Teaching English through Online Learning in The Covid-19 Pandemic at Public Vocational High Schools at Lubuklinggau” by the Main Supervisor Syaprizal, M.Pd and Counselor Supervisor Agus Triyogo, M.Pd ABSTRACT The purpose of this research was to find out (1). 1. What are the media used by the teacher through online learning in pandemic Covid 19, (2). What are the difficulties faced by teachers in using the media in pandemic Covid 19, (3). How the teachers control the student during online class in pandemic Covid 19. The research method used was a descriptive qualitative research. The subject of the research was 10 teachers of English at public vocational high school Lubuklinggau that were choosen by purposive data sampling. In collecting data, the research used (1). Interview the teachers who are chosen, (2). Making transcription from the interview with the teachers, (3). Encoding the collecting data, (4). Classifying of teachers’ media, (5). Analyzing the types of teachers' media online learning during the COVID-19 pandemic, (6). Concluding the data. The result showed that media used by the teachers through online learning during covid-19 pandemic and the difficulties faced by the teachers and also the teachers way to control the student through online learning during covid-19 pandemic at vocational high school at Lubuklinggau. Keywords: Media, Online learning